2013
DOI: 10.1123/jpah.10.4.496
|View full text |Cite
|
Sign up to set email alerts
|

School Physical Activity Policy Assessment

Abstract: Test-retest results suggest S-PAPA items are reliable and useful in assessing PA policies in elementary schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 12 publications
0
44
0
1
Order By: Relevance
“…Survey items were selected from the School Physical Activity Policy Assessment (S-PAPA) tool, 12 and some adaptations were made. The survey was kept brief to maximize response rate, and the items hypothesized to have the highest reach and impact on physical activity, based on findings from previous studies, were retained.…”
Section: Methodsmentioning
confidence: 99%
“…Survey items were selected from the School Physical Activity Policy Assessment (S-PAPA) tool, 12 and some adaptations were made. The survey was kept brief to maximize response rate, and the items hypothesized to have the highest reach and impact on physical activity, based on findings from previous studies, were retained.…”
Section: Methodsmentioning
confidence: 99%
“…An example of an item coded for duration was: “How long are the typical physical education class periods (counting time for changing/showering)?”13 An example of an item coded for frequency was: “How many physical education classes per week do students receive? (Provide the average)”14 An example of an item coded for scheduling was: “What type of class schedule do your students follow?”17 For the most part, as mentioned earlier these measures were not conceptualized specifically as implementation outcome measures in the various survey instruments assessed.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, apart from the study by Lounsbery et al, 83 which only reported on content validity for the S-PAPA tool, all the other studies examined additional validity types such as construct or criterion validity to establish stronger measurement proprieties of the newly developed tools. When validity was tested, construct validity was the most often reported validity type, which is an essential measurement property to establish if audit tools are expected to be used to evaluate the environmental characteristics in relation to health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-rater reliability (Table 2) was the most commonly tested type of reliability (n=7) 13, 21, 23-26 followed by test-retest (n=3), 21, 82, 83 and internal consistency (n=1). 25 For reliability assessment, studies reported Pearson correlation, Cronbach's α, kappa coefficient, percent agreement and/or interclass correlation coefficient (ICC) scores.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation